1985
DOI: 10.1007/bf00515562
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y (NPY) reduces field stimulation-evoked release of noradrenaline and enhances force of contraction in the rat portal vein

Abstract: The effect of neuropeptide Y (NPY) on fractional tritium-noradrenaline (3H-NA) release and contractile activity was studied in the isolated portal vein of SHR and WKY rats. NPY (5 X 10(-7) M) enhanced the force of the spontaneous contractile activity by about 40%. The fractional 3H-release elicited by transmural nerve stimulation (TNS), which mainly reflects 3H-NA, was reduced by about 40% after preincubation with 5 X 10(-7) M NPY in portal veins from both SHR and WKY rats. The inhibitory effect of NPY on TNS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…PYY and NPY are on the whole equipotent, whereas NPY 2-36 appears to be markedly less potent (Rioux et al, 1986). Moreover, NPY can inhibit the electrically-stimulated release of NA from sympathetic fibres in the vas deferens (Lundberg & Stjarne, 1984) and in certain blood vessels (Dahlof et al, 1985). This effect is mediated via Y2-receptors which recognize not only full length NPY/PYY but also C-terminal fragments of NPY and PYY (Wahlestedt et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…PYY and NPY are on the whole equipotent, whereas NPY 2-36 appears to be markedly less potent (Rioux et al, 1986). Moreover, NPY can inhibit the electrically-stimulated release of NA from sympathetic fibres in the vas deferens (Lundberg & Stjarne, 1984) and in certain blood vessels (Dahlof et al, 1985). This effect is mediated via Y2-receptors which recognize not only full length NPY/PYY but also C-terminal fragments of NPY and PYY (Wahlestedt et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Since exogenous NPY produces vasoconstriction via nonadrenergic mechanisms (Lundberg & Tatemoto, 1982), and since part of the sympathetic vasoconstrictor response to nerve stimulation has been shown to remain after combined alpha-and beta-adrenoceptor blockade or reserpine treatment, it has been suggested that NPY may be involved in sympathetic vascular control (see Lundberg et al, 1986d). NPY also seems to inhibit NA release via a prejunctional action (Lundberg & Stjarne, 1984; Dahlof et al, 1985). Thus, NPY may both modulate neurotransmitter release and contribute to the postjunctional response of vascular smooth muscle.…”
mentioning
confidence: 99%
“…Thus, NPY has been found to inhibit transmural nerve-stimulation evoked contraction of mouse and rat vas deferens, rat uterus, and rat and guinea pig heart, as well as mesenteric arteries [84][85][86][87][88]. The effect has been shown to be due to a presynaptic inhibitory action of the peptide on the release of noradrenaline [87][88][89]. In the isolated perfused mesenteric arterial bed of the rat, inhibition of the electrically stimulated release of noradrenaline was observed over a concentration range of NPY of 10 -1~ to 10 -7 M. The low concentrations (10 -1~ and 10 -9 M) decreased the effect of nerve stimulation on perfusion pressure, whereas the higher concentrations (10 .7 M) produced a marked potentiation [87].…”
Section: Presynaptic Effects Of Npymentioning
confidence: 97%